Glyceroglycolipids in marine algae: A review of their pharmacological activity - Guo, Sha-sha; Wang, Zhen-guo (Frontiers in Pharmacology, 2022)
Glyceroglycolipids are major metabolites of marine algae and have a wide range of applications in the medicine, cosmetics and chemistry research fields. They are located on the cell surface membranes. Together with glycoproteins and glycosaminoglycans, known as glycocalyx, they play critical roles in multiple cellular functions and signal transduction and have several biological properties such as anti-oxidant and anti-inflammatory properties, anti-viral activity, and anti-tumor immunity. This article focused on the sources and pharmacological effects of glyceroglycolipids, which are naturally present in various marine algae, including planktonic algae and benthic algae, with the aim to highlight the promising potential of glyceroglycolipids in clinical treatment.